Comparative study on the use of Moringa oleifera as natural coagulant and aluminium sulphate in restaurant wastewater treatment - Temitope, Adegoke Adedotun; Samuel, Lawal Nurudeen; Abosede, Odusanya Olubunmi; Toheeb, Idowu Olamilekan; Temitayo, Oyetunji Opeyemi (Penerbit Universiti Kebangsaan Malaysia, 2020)
The enormous amount of wastewater generated by restaurants often require some level of treatment before disposal. This is partly achieved by using synthetic coagulants with its attendant environmental risk. This study is aimed at investigating the use of Aluminium Sulphate (AS) and Moringa oleifera (MO) for treating restaurant wastewater (RW). Different doses (0, 50, 100, and 150 mg/l) of the prepared stock solution of AS and MO were applied to 1000 ml of RW collected from a University restaurant. The result showed that the treated sample pH reduced from 7.55 to 6.86 and 7.0 at an optimum dose of 150 and 50 ml for AS and MO while conductivity increased from 1.03 to 2.22 mg/l and 1.74 mg/l for AS and MO, respectively. Turbidity reduced from 44.73 mg/l to 5.20 mg/l for MO and 5.77 mg/l for AS; dissolved oxygen increased from 0.35 to 0.51 mg/l and 0.70 mg/l for MO and AS; Magnesium reduced from 21.11 to 14.77 mg/l for MO, but increased to 29.07 mg/l for AS; Zinc increased from 1.19 to 6.15 mg/l for MO and 7.10 mg/l for AS, while Calcium increased from 2.02 mg/l to 5.09 mg/l for MO, and 3.09 mg/l for AS. The MO seed extract achieved a better reduction of pH and turbidity at higher dose while no distinct trend was observed in all the parameters when AS was applied. Doses of MO seed extract can be further optimized and applied as a low cost option for RW treatment.